From data to information: a meta-legal framework to political-juridical analysis of digital transformation - Ana Cristina Aguilar Viana (International Journal of Digital Law)
The digital revolution has brought about challenges for the legal domain. Traditional legal frameworks struggle to address issues such as data privacy and security in the online environment. One problematic can be found in the limitation of the analysis of cyberspace, as well as the nature of the elements that compose it, as these are limited to binary classifications. This essay argues that a deeper understanding of the digital world, including the nature of data, information, and knowledge, is crucial for effective legal and policy analysis. By drawing on interdisciplinary perspectives, the essay proposes a richer and more nuanced approach to data governance, moving beyond the binary limitations of traditional legal frameworks. It highlights the importance of recognizing data as a relational and socio-technical value, with implications for both public and private actors.